ANALISIS KINERJA APRON MOVEMENT CONTROL TERKAIT SINGLE ACCOUNTABLE KEPALA BANDAR UDARA DALAM MENJAMIN KESELAMATAN PENERBANGAN DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK NUSA TENGGARA BARAT - M.Florian Rizqahul Ramhans; Hemi Pramuraharjo; Ichyu Machmiyana (Ikatan Dosen Menulis, 2025)
The aviation industry is experiencing rapid growth, demanding enhanced safety standards, particularly in airport airside operational supervision. This study aims to analyze the performance of Apron Movement Control (AMC) in monitoring Ground Support Equipment (GSE) and to evaluate the role of the General Manager as Single Accountable in ensuring aviation safety at Zainuddin Abdul Madjid International Airport, Lombok. This research employed a descriptive qualitative method using observations, semi-structured interviews, and documentation. The results indicate that AMC has routinely conducted supervision through Random Ramp Checks; however, violations of GSE feasibility standards such as oil leaks, malfunctioning indicator lights, and expired fire extinguishers are still found. These findings reveal that AMC's supervision is not yet optimal in ensuring GSE operational eligibility. Furthermore, the General Manager’s role as Single Accountable has not been effectively realized due to weak enforcement following AMC’s reports. The study concludes that GSE supervision effectiveness can be improved if AMC’s operational supervision is supported by the firm enforcement of operational discipline by the General Manager as the sole party responsible for aviation safety.